Childhood Intussusception: Timely Management Leads to Decreased Surgical Risk - Dr. Arun Kumar Gupta, Dr. Vinita Chaturv, Dr. Sunil Kumar Mehra, Dr. Dinesh Kumar Barolia, (International Journal of Innovative Research in Medical Science, 2018)
Intussusception is the most common cause of intestinal obstruction in infants and children in < 1yr of age (1). Intussusception cases usually reported late therefore operative procedure was inevitable and results in significant morbidity and mortality. By this study we emphasized on timely transfer of intussusception case to a pediatric surgical center so as to decrease surgical risk. The surgical morbidity was low in those who were admitted early or directly to our center. Methods - We retrospectively reviewed cases of intussusception in children <15 years. Children were treated from October 2015 to December 2107 at pediatric surgery department of SMS medical college Jaipur Rajasthan. Age, sex, month of admission, symptom with duration, diagnostic methods, and treatment modalities were recorded and analyzed. Results - We studied 300 patients with intussusception.272 (90%) were treated surgically. We recently started ultrasonography guided pneumatic reduction and 24(85.7%) out of 28 treated successfully by it. Out of the patients requiring surgery 202 (67.34%) patients were reduced by per-operative manual reduction and in 60(22%) patients resection and anastomosis with 10(3.6%) treated with resection and ileostomy. 25.34% cases have delayed diagnosis and lately transferred from peripheral hospitals requiring resection and diversion. Conclusion - In conclusion, Intussusception cases usually reported late therefore high likelihood of surgical management. The patients who underwent resection have longer duration of hospital stay.